MMP3 is a reliable marker for disease activity, radiological monitoring, disease outcome predictability, and therapeutic response in rheumatoid arthritis. Issue 4 (August 2018) - Lerner, Aaron; Neidhöfer, Sandra; Reuter, Sandra; Matthias, Torsten
Abstract: Matrix metalloproteinase-3 or MMP3 also known as stromelysin-1 is an enzyme that is actively involved in joint destruction in rheumatoid arthritis (RA) patients. Screening the last three decades, it appears that serum levels of MMP3 reflect positively RA disease activity, joint and bone injury, and radiological erosion and predict disease outcome and drug responsiveness as summarized in several publications reporting outcomes on more than 8000 patients with RA. MMP-3 monitoring should be embedded in the routine assessment and accompany therapeutic modalities, in personalized medical RA management.